Integrating Reader Response Theory into EFL Classroom at Farhangian University - Rahimipour, Saeid (AJELP: Asian Journal of English Language and Pedagogy, 2021)
The integration of literature in TEFL has recently achieved a profound status. The applicability and efficiency of RRT in EFL settings are great educational objectives. This article deals with the introduction of Reader Response Theory to language teaching in Teacher Training Centers. The subjects were 120 sophomore students at Farhangian University, Shahid Modaress and Imam Jafar-e-Sadegh Campuses. An experimental design was used in the study. Instead of offering the regular teaching textbooks, eight grade-three short stories were presented for language teaching purposes. The data analysis revealed that the application of RRA to teaching general English in Farhangian University proved to be highly successful and it improved the learners’ language learning significantly. This proved to be highly successful with girls than boys. The incorporation of Reader Response Theory is highly recommended in university curriculum for better language learning and teaching.